2022
DOI: 10.18632/oncotarget.28100
|View full text |Cite
|
Sign up to set email alerts
|

The “Immunoscore” in rectal cancer: could we search quality beyond quantity of life?

Abstract: Because of the function and anatomical environment of the rectum, therapeutic strategies for local advanced rectal cancer (LARC) must deal with two challenging stressors that are a high-risk of local and distal recurrences and a high-risk of poor quality of life (QoL). Over the last three decades, advances in screening tests, therapies, and combined-modality treatment options and strategies have improved the prognosis of patients with LARC. However, owing to the heterogeneous nature of LARC and genetic status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 111 publications
(129 reference statements)
1
2
0
Order By: Relevance
“… 35 , 39 , 41 , 42 A biopsy-adapted IS could possibly even aid with predicting therapy response in rectal cancer patients. 43 , 44 Together with our observation, that hyperplasia of the LN paracortex (also known as a T-cell zone) relates to prolonged survival, this underlines that the host antitumor response probably is more than a local response and LNs play an important in the immunological reaction to the tumor.…”
Section: Discussionsupporting
confidence: 57%
“… 35 , 39 , 41 , 42 A biopsy-adapted IS could possibly even aid with predicting therapy response in rectal cancer patients. 43 , 44 Together with our observation, that hyperplasia of the LN paracortex (also known as a T-cell zone) relates to prolonged survival, this underlines that the host antitumor response probably is more than a local response and LNs play an important in the immunological reaction to the tumor.…”
Section: Discussionsupporting
confidence: 57%
“…In the recent RAPIDO trial 37 , the experimental TNT group increased the rate of pCR and decreased the rate of distant metastases compared to the conventional approach. On the other hand, some studies have shown that an “immunoscore” 38 , calculated with counts of CD8+ or FoxP3+ regulatory T cells, outperformed the traditional TNM staging in predicting outcomes in CCR 39 and a plethora of immune checkpoint inhibitors and other immunotherapies are emerging 40 . Therefore, it seems relevant to assess the impact of inflammatory markers in the subtyping of disease to select the best strategy for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5 , these findings can explain why women have a better outcome than male patients with rectal cancer and are particularly relevant since several trials are now ongoing testing immune checkpoint inhibitors in CRC, calling for reliable predictors of therapy response 36 . Moreover, the analysis of TME has been proposed to predict response to chemotherapy in CRC patients, and the immunoscore is currently being tested as a potential predictor of response to neoadjuvant chemoradiotherapy in LARC 37 . Based on the results of our study and as proposed by other authors 6 , sex should be considered when defining the treatment strategy of rectal cancer patients or designing prognostic scores, acknowledging the significant differences in epidemiology, cancer biology, and response to therapy.…”
Section: Discussionmentioning
confidence: 99%